Pengaruh Model Pembelajaran Kooperatif Terhadap Hasil Belajar Pukulan Jab Dan Stright Pada Mata Kuliah Tinju Mahasiswa Jurusan Pendidikan Jasmani Fakultas Olahraga Dan Kesehatan Universitas Negeri Gorontalo - Lamusu, Zulkifli A. (-, 2025)
This study aims to analyse the effect of cooperative learning models on the learning outcomes of Jab and Straight punches among students in the Physical Education Department, Faculty of Sports and Health, Gorontalo State University. This study uses a quantitative method with an experimental design. The population in this study consists of 72 students, while the sample consists of 20 students selected using purposive sampling techniques. Data collection was conducted through skill tests before and after the implementation of the cooperative learning model, which were then analysed using a t-test with a significance level of 0.05. The results of the study indicate that there is a significant effect of the cooperative learning model on the improvement of basic jab and straight punch techniques. The average pre-test score was 7.35 with a standard deviation of 2.1, while the average post-test score increased to 12.2 with a standard deviation of 2.26. The analysis of variance yielded a t-value of 9.7, which is greater than the critical t-value of 2.86, thus rejecting the null hypothesis and accepting the alternative hypothesis. Thus, it can be concluded that the cooperative learning model can influence the learning outcomes of jab and straight punches among students in the Physical Education Department of the Faculty of Sports and Health at Gorontalo State University, as evidenced by the significant improvement in learning outcomes for jab and straight punches. The main attractive factor of this learning model is the encouragement of social interaction among students, cooperation in small groups, and a deeper understanding, enabling students to master the techniques more optimally.